Exploring How Systemic Racism Affects African American Students’ College Choice Decisions: A Comparative Case Study Analysis - Timothy P. Yancy (European Scientific Journal, ESJ, 2023)
A lot of attention has been given to the problem of institutionalized racism in academia lately. From a young age, the road to success in school has not always been an easy route for African American students. According to Bottiani, Bradshaw, and Mendelson (2016), students' perceptions of differential treatment, exclusion, and discrimination by teachers and adults in school appear to play a significant role in the poor outcomes among the youth of color. The climate change surrounding racial issues and U.S. economic downturn have had a significant impact on students of color as regards to their commitment to higher education (Karkouti, 2016). This paper attempts to answer the overarching research question such as: How does systemic racism play a role in African American students' college choice decisions? The results from this paper are displayed in critical race theory, as it is a crucial factor in the analysis of choice theory.